Color Tuning of Nanofibers by Periodic Organic–Organic Hetero-Epitaxy - Simbrunner, Clemens (American Chemical Society, 2012)
[Image: see text] We report on the epitaxial growth of periodic para-hexaphenyl (p-6P)/α-sexi-thiophene (6T) multilayer heterostructures on top of p-6P nanotemplates. By the chosen approach, 6T molecules are forced to align parallel to the p-6P template molecules, which yields highly polarized photoluminescence (PL)-emission of both species. The PL spectra show that the fabricated multilayer structures provide optical emission from two different 6T phases, interfacial 6T molecules, and 3-dimensional crystallites. By a periodical deposition of 6T monolayers and p-6P spacers it is demonstrated that the strongly polarized spectral contribution of interfacial 6T can be precisely controlled and amplified. By analyzing the PL emission of both 6T phases as a function of p-6P spacer thickness (Δd(p–6P)) we have determined a critical value of Δd(p–6P )≈ 2.73 nm where interfacial 6T runs into saturation and the surplus of 6T starts to cluster in 3-dimensional crystallites. These results are further substantiated by UPS and XRD measurements. Moreover, it is demonstrated by morphological investigations, provided by scanning force microscopy and fluorescence microscopy, that periodical deposition of 6T and p-6P leads to a significant improvement of homogeneity in PL-emission and morphology of nanofibers. Photoluminescence excitation experiments in combination with time-resolved photoluminescence demonstrate that the spectral emission of the organic multilayer nanofibers is dominated by a resonant energy transfer from p-6P host- to 6T guest-molecules. The sensitization time of the 6T emission in the 6T/p-6P multilayer structures depends on the p-6P spacer thickness, and can be explained by well separated layers of host–guest molecules obtained by organic–organic heteroepitaxy. The spectral emission and consequently the fluorescent color of the nanofibers can be efficiently tuned from the blue via white to the yellow-green spectral range.